Analysis of Student Interest in Using PSIM Trainers and Applications in Power Electronics Courses - Assyifa, Marda; Hari Anna Lastya (PTE FTK UIN Ar-Raniry, 2025)
Practicum in power electronics course is one of the courses that has an important role in understanding the basics of electrical energy conversion systems, and the use of educational technology based on teaching aids in the form of trainers and PSIM applications to improve students' understanding of the concepts taught. This study aims to determine the extent to which students are interested and feel helped by the use of trainers and PSIM applications in Power Electronics courses. The researcher used a qualitative method with a descriptive type. This study used an interview instrument. The subjects of this study were students of the Electrical Engineering Education study program at UIN Ar-Raniry Banda Aceh who had taken the Power Electronics course, totaling 10 people. The results of the study showed that there was a comparison of the interests of Electrical Engineering Education students, namely out of 10 students, 7 of them were interested in using trainers and 3 of them were interested in PSIM application software. So from this study it was found that Electrical Engineering Education students were more interested in using trainers than PSIM application software in the Power Electronics course